Louis PASTEUR was a pioneer of crystallography, bacteriology, industrial microbiology, immunology. To the 200th anniversary of his birth - Iutynska, G.A.; Іутинська, Г.О. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
The name of Louis Pasteur, a world-renowned microbiologist, is now known to every educated person. His experiments that led to the discovery of the world of microbes and their role in our lives are described in many textbooks and reference books. For biologists it is interesting to know about this man as a person, his life path, beliefs, and worldview.